(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the activation of word formation in the Russian language of the 21st century, based on the analysis of the National Corpus of the Russian Language and online resources. The reader will learn about the most productive ways of forming new words — affixation, abbreviations, acronyms, and borrowings, including Anglicisms. The study highlights age-related characteristics in the use of neologisms, as well as the influence of the digital environment, social networks, and online media on their dissemination. The article provides valuable data for understanding the dynamics of the modern Russian language, its adaptation to globalization and digitalization, and also serves as a practical resource for teachers, linguists, and language researchers.